2011
DOI: 10.1371/journal.pone.0016844
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Burden and Socioeconomic Status in India

Abstract: BackgroundThe dimensions along which mortality is patterned in India remains unclear. We examined the specific contribution of social castes, household income, assets, and monthly per capita consumption to mortality differentials in India.Methods and FindingsCross-sectional data on 217 363 individuals from 41 554 households from the 2004–2005 India Human Development Survey was analyzed using multiple logistic regressions. Mortality differentials across social castes were attenuated after adjusting for househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 16 publications
4
35
1
Order By: Relevance
“…Mortality accessed in three studies reported odd ratios (OR) varying from 1.08 to 1.94. 19,22,12 Po and Subramanian (2011) reported significantly higher odds of mortality in Other Backward Classes (OBC), Scheduled Castes (SC), and Scheduled Tribes (ST). 19 However, after adjusting for wealth factors such as income, assets, and consumption per capita, the associations were no longer statistically significant with the exception of Scheduled Castes (OR = 1.72, 95% CI = 1.23-2.41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality accessed in three studies reported odd ratios (OR) varying from 1.08 to 1.94. 19,22,12 Po and Subramanian (2011) reported significantly higher odds of mortality in Other Backward Classes (OBC), Scheduled Castes (SC), and Scheduled Tribes (ST). 19 However, after adjusting for wealth factors such as income, assets, and consumption per capita, the associations were no longer statistically significant with the exception of Scheduled Castes (OR = 1.72, 95% CI = 1.23-2.41).…”
Section: Resultsmentioning
confidence: 99%
“…19,22,12 Po and Subramanian (2011) reported significantly higher odds of mortality in Other Backward Classes (OBC), Scheduled Castes (SC), and Scheduled Tribes (ST). 19 However, after adjusting for wealth factors such as income, assets, and consumption per capita, the associations were no longer statistically significant with the exception of Scheduled Castes (OR = 1.72, 95% CI = 1.23-2.41). Adjusting the effect of caste on mortality with household income and asset ownership independently also resulted in the attenuation of caste effect on mortality except in Scheduled Castes as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The previous empirical research has established a strong connection between 'international income inequality and inequality in health'. The studies have shown that common indicators of population health such as life expectancy and infant mortality are strongly correlated with average income levels, such that richer countries enjoy better health (Preston, 1975;Deaton, 2004;Subramanian et al, 2006Subramanian et al, , 2009Harper and Lynch, 2007;Van de Poel et al, 2008;Subramanian, 2008;Speybroeck et al, 2009;Konda et al, 2009;Po and Subramanian, 2010). Also, the evidence from trends in health inequalities-in both the developing and developed world-supports the notion that health inequalities rise with rising per capita income.…”
Section: Discussionmentioning
confidence: 87%
“…Though, socioeconomic status and health outcomes, health inequalities relationship are well established (Wagstaff and Doorslaer, 1991;Kakwani et al, 1997;Gwatkin, 2000;Kawachi et al, 2002;Wagstaff, 2002aWagstaff, , 2002bMormot, 2002;Van Doorslaer and Gerdtham, 2003;Wagstaff et al, 2003;Mackenbach, 2003;Van Doorslaer et al, 2004;Subramanian and Kawachi, 2004;Hosseinpoor et al, 2006;Subramanian et al, 2006Subramanian et al, , 2009Harper and Lynch, 2007;Van de Poel et al, 2008;Subramanian, 2008;Speybroeck et al, 2009;Konda et al, 2009;Po and Subramanian, 2010;Pradhan and Arokisamy, 2010;Marmot, 2005Marmot, , 2010Po and Subramanian, 2011;Arokiasamy et al, 2012;Suzuki et al, 2012), but there are not many studies which have examined the relationship between the demographic and health transition with transition health inequalities. In particular, the question 'Does socioeconomic, demographic and health progress is leading to greater uniformity in average health status or health inequalities are swimming against the tide' is not given much attention.…”
Section: Health Inequalities Versus Socioeconomic Demographic Healtmentioning
confidence: 99%
See 1 more Smart Citation